The Effect of Profitability and Leverage on Profit Management in Manufacturing Companies Listed on the Indonesia Stock Exchange - Aminuddin Hamdat; Muh. Rizal; Murdin Muchsidin; Muspa; Fathu Ramadhani (Formosa Journal of Sustainable Research, 2023)
Financial statements are information that describes the condition of the company and can be used as an illustration of the company's performance. This condition will motivate company managers of certain strategies to generate profits that are in line with investor expectations. Profit management in practice can occur agency conflicts depicted in agency theori. Profit management practices can affect the reasonableness of the presentation of financial statements that can mislead users when they should be useful to users. This study aims to determine the effect of profitability and partial leverage on profit management in manufacturing companies on the Indonesia Stock Exchange. The analysis method used is multiple linear regression analysis with the help of SPSS version 22.0. The observation period carried out is 4 years, namely 2016 to 2019. The results show that partially profitability has a positive effect on profit management in manufacturing companies listed on the Indonesia Stock Exchange. Leverage has an insignificant positive effect on profit management in manufacturing companies listed on the Indonesia Stock Exchange